Penggunaan Gadget pada Anak: Hubungan Pengawasan dan Interaksi Orang Tua terhadap Perkembangan Bicara dan Bahasa Anak - Aulia Septyani, Reta; Lestari, Pudji; Suryawan, Ahmad (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
Lack of supervision on gadgets can affect children's speech and language development, especially without interaction with parents. This study aimed to analyze the relationship between parental supervision and interaction with gadgets in children aged 4-5 years with the risk of speech and language development delays. The method used in this research is observational analytic. In analyzing the data, this study uses non-parametric statistical test Chi Square. The results of this study found that most respondents with speech and language development results are at risk of being late, rarely get supervision from their parents when using gadgets, namely, 23 respondents (79.31%), and most of the respondents' parents also said they did not interact when their children were using gadgets. gadgets as many as 23 respondents (79.31%). So that we get the results that there is a relationship between supervision (p value 0.001 < 0.05) and interaction (p value 0.000 < 0.05) of parents and children when using gadgets with children's speech and language development. Supervision and parental interaction on the use of gadgets in children are very important, considering the age of 4-5 years is included in the golden age where this period is a very sensitive developmental period because it will affect the future development of children. The findings in this study are expected to provide implications for parents to be able to increase supervision and interact with the use of gadgets in children.